Global issues and financing for achieving sustainable development goals - Unmana Sarangi (Dutch Journal of Finance and Management, 2020)
The research paper entitled 'Global Issues and Financing for Achieving Sustainable Development Goals' is a unique research effort to analyze the current frontline global issues that is affecting the global economies at large. In these days of current global crisis, the COVID-19 global pandemic has emerged as not only a global health crisis but also a global humanitarian crisis. The research has made an attempt to study and analyze the cross cutting global issues including the present global pandemic which has taken a serious toll on humanity, but has also affected the various sectors of the global economies such as health, humanitarian, economic, social, geopolitical, environment etc., and other related cross-cutting issues which are vital determinants and key indicators in achieving the Sustainable Development Goals(SDGs). The paper also dwells into the aspect of global financing issues keeping in mind and including finding ways and means for containment of the present global health pandemic by looking into the various aspects of financing needs of the economies to enable these economies to come out of such serious economic shocks that has resulted and affected these economies due to the severe outbreak of COVID-19. The research paper also covers and studies other aspects of the global economies such as the Addis Ababa Action Agenda(AAAA) on cross cutting initiatives to develop and built-in synergies for achieving the SDGs, monitoring by the Inter-Agency Task Force on Sustainable Development and the Financing for Global Sustainable Forum(FfSD), upcoming events planned by FfSD, Global issues for FfSD Forum, ECOSOC and its role on International Cooperation in Tax Matters, Global Economic Governance, External Debt, Innovative Financing for Sustainable Development including Inclusive and Local Finance, Global Investors for Sustainable Development Alliance, key messages conveyed by the United Nations in their report on Financing for Global Sustainable Development 2020, important statements made by global experts of United Nations on issues pertaining to financing for achieving SDGs, COVID-19 and it impact on humanity in terms of human crisis, global health crisis and concerns, socio-economic and environmental aspects for sustainable long-term financing in various economies including the undeveloped LLDCs, SIDSs, African & Caribbean economies and the developing economies. The role of international multilateral institutions such as the World Bank, IMF, IFC, MIGA and other global financing institutions are of paramount importance in terms of financing these economies to come out of the global pandemic at the first instance and then in stabilizing these economies in the long-run. The important policy considerations and conclusions drawn from the research study is that the WHO and United Nations including other multilateral and financing institutions need to work in tandem not only to aid these economies to come out of the global pandemic, but also to strike a balance in terms of achieving the long-term SDGs slated by UN which are key indicators and determinants in achieving the SDGs in these economies.
Keywords: 650; COVID-19 pandemic; SDGs; FfSDR; International Tax Cooperation; Global Investors Sustainable Alliance; Global Aspirations